The size of the underground economy in Germany: A correction of the record and new evidence from the Modified-Cash-Deposit-Ratio approach - Michael Pickhardt; Jordi Sarda (Westfälische Wilhelms-Universität Münster, Centrum für Angewandte Wirtschaftsforschung (CAWM), 2010)
Based on the Ahumada et al. (2007, Review of Income and Wealth) critique we revise existing estimates of the size of the German underground economy. Among other things, it turns out that most of these estimates are untenable and that the tax pressure induced size of the German underground economy may be much lower than previously thought. To this extent, German policy and law makers have been misguided during the last three decades. Therefore, we introduce the Modified-Cash-Deposit-Ratio (MCDR) approach, which is not subject to the recent critique and apply it to Germany for the period 1960 to 2008.
Keywords: O17; Q41; C22; 330; underground economy; shadow economy; cash-depositratio; currency demand approach; MIMIC approach